A comparative study of dairy whipping cream and palm oil-based whipping cream in terms of FA composition and foam stability - Shamsi, K.; Che Man, Y. B.; Yusoff, M. S. A.; S., Jinap (Wiley, 2002)
Nondairy creams are more stable than dairy creams, especially in hot climates. This paper considers the reasons for this stability and which FA is most suitable for producing this effect in palm oil and palm kernel oil‐based whipping cream. The results show that an increase in unsaturated FA, particularly oleic acid, can produce a more stable foam in whipping cream. This study also shows that an increase in iodine value has a positive impact on the stability of foam in nondairy whipping cream as well. This study points out the advantages of a palm oil‐based whipping cream over commercial dairy whipping cream, particularly when the stability of the foam is important and the product is supposed to be consumed in hot weather.